MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS, SELF-CONFIDENCE SISWA MELALUI PENERAPAN PENDEKATAN PEMBELAJARAN SAINTIFIK BERBANTUAN PERSOALAN OPEN-ENDED - Nurhayati, Aat (2015)
Abstract - This research reports the result of scientific approach learning with open-ended problems experiment of mathematical connection ability and self-confidence of junior high school students. The study used three instruments: a set of pre-test, a set of post-test and likert-scale. The research found the following: (a) the experiment students have better mathematical connection ability achievement than those of control ones, (b) the experiment students have better mathematical connection ability enhancement than those of control ones, (c) the experiment students have better self-confidence than those of control ones. Index Term: Scientific approach, open-ended problem, mathematical connection ability, self-confidence